1998
DOI: 10.1074/jbc.273.9.4864
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Tryparedoxin Peroxidase Gene fromCrithidia fasciculata and Its Functional Expression in Escherichia coli

Abstract: Tryparedoxin peroxidase from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…Despite the use of His-tagged proteins, the Prx activities are assumed to be similar to those of native Prxs as shown in the comparative work with Prxs of Crithidia fasciculata by Montemartini et al (1998), in which N-terminally His-tagged Prx was shown to be as active as the purified Prx protein. Nevertheless, the use of His-tagged proteins should be kept in mind and the enzymic data interpreted with caution.…”
Section: The Catalytic Activity Of Prxmentioning
confidence: 99%
“…Despite the use of His-tagged proteins, the Prx activities are assumed to be similar to those of native Prxs as shown in the comparative work with Prxs of Crithidia fasciculata by Montemartini et al (1998), in which N-terminally His-tagged Prx was shown to be as active as the purified Prx protein. Nevertheless, the use of His-tagged proteins should be kept in mind and the enzymic data interpreted with caution.…”
Section: The Catalytic Activity Of Prxmentioning
confidence: 99%
“…The medically important trypanosomatids do not contain catalase, glutathione peroxidase, or glutathione reductase but rely on an analogous system to regulate oxidative stress. The details of this trypanothione peroxidase system have been elucidated in the model trypanosome Crithidia fasciculata (6,8,10,11) and are shown in Fig. 1.…”
mentioning
confidence: 99%
“…All three TXNs have been shown to be specifically reduced by trypanothione with comparably low K m values. TXN1 and TXN2 can substitute for each other in the reduction of tryparedoxin peroxidase [11], whereas the TXN of T. brucei was reported to act as a reducing substrate for the ribonucleotide reductase [9]. It appears conceivable that the diversification of the TXNs provides the basis for functional specialization allowing specific reduction of distinct disulfides at the expense of trypanothione.…”
Section: Discussionmentioning
confidence: 99%
“…The correspondence of the deduced amino acid sequence with the peptides derived from authentic TXN1 leaves no doubt that this time we have indeed cloned the TXN1 gene. The single amino acid exchange detected at position 142 is either explained by the ambiguities resulting from sequencing traces of peptides or due to common microheterogeneities in variable regions of kinetoplast proteins encoded by multicopy genes [11,14]. The availability of three distinct TXN sequences now allows a better classification of these novel proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation